Objek Wisata Kawah Putih: Peran Kawah Putih Dalam Meningkatkan Ekonomi Lokal Melalui Pariwisata - Erika Rahmadani; Naila Priska Amelia (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2024)
This research aims to improve the local economy of the community through White Crater tourism. In addition, this study also analyzes the local economy in the White Crater area through tourism and examines the impacts on the local economy. The background of this study is that the White Crater, located in the Ciwidey area of West Java, has a main attraction, which is the volcanic crater with greenish-colored water that changes according to the weather, and contains sulfur. The White Crater supports the development of local tourism and contributes to the economic improvement of the surrounding community. Local people can seize job opportunities, such as providing transportation, becoming tour guides, or selling local food and handicrafts. However, there are several issues found in the field, including: 1) The large number of tourists can lead to ecosystem damage, pollution, and diminish the beauty of the White Crater, 2) The lack of supporting facilities such as road access, public transportation, and parking spaces, which could reduce the tourist appeal, and 3) The lack of coordination between local government, the management of the White Crater, and the local community, resulting in frequent obstacles to tourism development. The method used in this study is a literature review to gather data and information. The findings of this research indicate that the White Crater creates job opportunities for the local community, which improves the local economy. However, there are environmental challenges due to uncontrolled tourist activities, leading to ecosystem damage. Furthermore, this study recommends that tourism management involve the local community as part of the management team, improve the road access to the tourist site, provide spacious parking, maintain clean public toilets, and place trash bins at every location.